Divergence and diversity in the Euro Area: The case of Germany, France and Italy - Paweł Tokarski (Stiftung Wissenschaft und Politik (SWP), 2019)
When the European Union introduced a common currency, this was based on the assumption that there would be increasing economic convergence of the participating states. These expectations were not met. Instead of gradually converging, the economic performance of euro area countries has noticeably diverged. The most considerable problem arising from this divergence is that it leads to social differences and to discrepancies in political interests regarding further direction of economic integration. Thus, in the long term, the current integration model within the euro area might be called into question. Previous analyses of economic differences in the euro area have mostly focused on specific groups of countries, such as southern Europe versus northern Europe or central versus peripheral Europe. This study takes a different approach to the issue of convergence by looking at the three largest economies in the euro area: Germany, France and Italy.
Keywords: 320